2023
DOI: 10.1558/jsrnc.21211
|View full text |Cite
|
Sign up to set email alerts
|

Humans and Nature

Frans Wijsen,
Zainal Abidin Bagir,
Mohamad Yusuf
et al.

Abstract: The Human and Nature scale (HaN scale) was developed in the Western context to investigate the relationship between ideas about nature and landscape planning. This pilot study expands the HaN scale and includes religion as an independent variable to investigate perceptions of human-nature relations in Indonesia. It examines how religious affiliation and religious practices influence visions of human-nature relations. This study shows that religious affiliation makes no difference. Muslims, Catholics, Protestan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We found that most respondents supported a nature-centric version of stewardship, thus not a type of steward that is master over or leader of nature, but a steward as partner of or participant in nature (Wijsen et al, 2023). In this paper we aim to acquire deeper insight into this finding making use of the qualitative research.…”
Section: Theory and Methodsmentioning
confidence: 95%
“…We found that most respondents supported a nature-centric version of stewardship, thus not a type of steward that is master over or leader of nature, but a steward as partner of or participant in nature (Wijsen et al, 2023). In this paper we aim to acquire deeper insight into this finding making use of the qualitative research.…”
Section: Theory and Methodsmentioning
confidence: 95%